2020
DOI: 10.1186/s13024-020-00378-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial involvement in Alzheimer disease development and progression

Abstract: Alzheimer disease (AD) is the most prominent form of dementia and the 5th leading cause of death in individuals over 65. AD is a complex disease stemming from genetic, environmental, and lifestyle factors. It is known that AD patients have increased levels of senile plaques, neurofibrillary tangles, and neuroinflammation; however, the mechanism(s) by which the plaques, tangles, and neuroinflammation manifest remain elusive. A recent hypothesis has emerged that resident bacterial populations contribute to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 126 publications
0
55
0
1
Order By: Relevance
“…The infection hypothesis was proposed decades ago when it became clear that there should be some triggering events at some points of the disease progression. 7 , 145–147 It is noteworthy that Oskar Fisher, in the same epoch as Alois Alzheimer, had already evoked this possibility. 148 Early evidence was done on HSV-1 viruses.…”
Section: Experimental Data Substantially Support the Infection Hypothesis Of Admentioning
confidence: 99%
“…The infection hypothesis was proposed decades ago when it became clear that there should be some triggering events at some points of the disease progression. 7 , 145–147 It is noteworthy that Oskar Fisher, in the same epoch as Alois Alzheimer, had already evoked this possibility. 148 Early evidence was done on HSV-1 viruses.…”
Section: Experimental Data Substantially Support the Infection Hypothesis Of Admentioning
confidence: 99%
“…There are little approved treatments can reverse or prevent the development of this disease ( Scheltens et al, 2016 ; Hodson, 2018 ; Long and Holtzman, 2019 ). The pathological feature of AD is abnormal folding and deposition of amyloid plaques (Amyloid β, Aβ) leads to formation of senile plaque (SP), and the accumulation of tau protein leads to neurofibrillary tangles (NFT) ( Simard et al, 2006 ; Bulgart et al, 2020 ). Aβ 42 fibrils is a major component of amyloid plaques and appears central to AD pathogenesis ( Fagan et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of direct effects, pathogenic oral microbes affect the occurrence of AD by entering the brain tissue through different paths and directly damaging the CNS (Parahitiyawa et al, 2009;Teixeira et al, 2017;Bulgart et al, 2020). Hemorrhagic oral treatment such as tooth extraction or transient bacteremia caused by gingivitis and periodontitis allows pathogenic microorganisms to break through the oral mucosal barrier and invade the bloodstream.…”
Section: The Direct Effect Of Oral Microbes On Admentioning
confidence: 99%
“…Oral microorganisms can also enter the brain through the trigeminal nerve, which are connected to the brain (Teixeira et al, 2017). Microbes entering the brain tissue and the pro-inflammatory factors they released further trigger an immune cascade, which includes the activation of microglia, inflammatory responses, and the activation of the complement system (Bulgart et al, 2020). Studies have also suggested that Aβ protein, which functions as an antibacterial peptide in innate immunity, may inhibit neuroinflammation to a certain extent and play a protective role in the brain.…”
Section: The Direct Effect Of Oral Microbes On Admentioning
confidence: 99%